DAMPAK PANDEMIC COVID 19 TERHADAP TINGKAT KECEMASAN IBU HAMIL DI KOTA BENGKULU - Annuril, Kheli Fitria; Hermansyah, Hermansyah (LPPM STIKES BHAKTI HUSADA BENGKULU, 2022)
Pendahuluan : Kesehatan mental ibu selama kehamilan dapat mempengaruhi kondisi psikologis, emosional, serta perkembangan sosial bagi ibu dan bayinya terutama di saat pandemi. Penelitian ini bertujuan untuk melihat bagaimana keadaan mental ibu hamil/ tingkat kecemasan selama masa pandemic covid 19 di Kota Bengkulu.Metode : Jenis penelitian ini adalah survey analitik dengan dengan desain Cross Sectional. Populasi adalah seluruh ibu hamil yang ada di Kota Bengkulu. Penelitian ini dilakukan di Bidan Praktik mandiri (BPM) Susi dan Klinik Mutiara Agma Betungan (BPM Herma Nelis) pada Bulan September-Nopember 2021. Teknik Sampling, yaitu non random sampling dengan metode purposive sampling dan jumlah sampel sebanyak 82 orang. Analisis data menggunakan ukuran proporsi dan ukuran pemusatan dan Bivariat dengan Chi Square pada α 5% dan analisis Multivariat dengan menggunakan Uji Regresi Logistik berganda.Hasil : Hasil penelitian diperoleh Sebagian besar responden mengalami kecemasan dalam kategori rendah serta tidak ada hubungan antara karakteristik ibu dengan tingkat kecemasan ibu hamil selama masa pandemic Covid 19.Simpulan : ada hubungan antara karakteristik ibu dengan kondisi mental ibu hamil/ tingkat kecemasan ibu selama masa pandemic Covid 19Kata kunci: dampak pandemi covid 19, kecemasan, ibu hamil ABSTRACT Introduction : The mother's mental health during pregnancy can affect the psychological, emotional, and social development conditions for mothers and their babies, especially during a pandemic. This study aims to see how the mental state of pregnant women / anxiety levels during the Covid-19 pandemic in Bengkulu City. This type of research is an analytical survey with a Cross Sectional design. The population is all pregnant women in Bengkulu City. Methods : Sampling Technique, which is non-random sampling with purposive sampling method and the number of samples is 82 people. The research instrument uses a questionnaire, NuPDQ in Indonesian developed by Dr. Marci Lobel and colleagues and translated and tested for validity by Santoso, which was designed in a google form. Data is processed with computer programs, presented univariately in the form of tables and graphs. Results :Data analysis using proportional measures and measures of centering and Bivariate with Chi Square at a α 5% and Multivariate analysis using multiple Logistic Regression Tests. The results of the study were obtained Most respondents experienced anxiety in the low category and there was no relationship between maternal characteristics and the anxiety levels of pregnant women during the Covid 19 pandemic. Conclusion :there is a relationship between the characteristics of the mother and the mental condition of pregnant women/the level of anxiety of the mother during the Covid 19 pandemicKeyword: covid 19 pandemic, anxiety, pregnant mother